SOSIALISASI LATIHAN PENCATATAN KEUANGAN SEDERHANA PADA PEDAGANG TOKO KELONTONG DI SAMARINDA - Wahyuti, Sri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2023)
This service aims to provide training socialization, namely to provide soft skills for Peek MSME actors in terms of simple financial recording. This training had a positive impact on MSME actors in the form of increasing their understanding of how financial records should be carried out for more effective business financial management. Training activities are carried out using socialization techniques and practice. The result of this training is that peep business actors have better skills in carrying out simple financial records. The main problem faced by MSME actors is that they have never recorded financial transactions in a simple and chronological manner so that the financial condition and development of the business cannot be known. With this activity, it is expected to increase understanding, knowledge, and skills in simple bookkeeping for grocery traders.